Dinofurcula cf. ventralis in the central coast of Peru and the first report of two Protoperidinium species - Ochoa, Noemí (2005)
This paper report Dinofurcula cf. ventralis, a very rare dinoflagellate that has not been recorded for Peruvian Pacific since their original description. Also, it reports Protoperidinium thulesense and Protoperidinium paulseni for the first time in Peru. The observations proceeded of the samples collected periodically between 1992-2004 in the Ancón Bay (77º11' W −11º46' S).